2021
DOI: 10.1108/apjba-01-2021-0019
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the luxury purchase intentions of young consumers: a qualitative analysis

Abstract: PurposeThe study intends to investigate the key purchase drivers of luxury brands in India. Given that a major segment of this target audience is the young consumers, the study focuses on determining these antecedents of luxury purchase from a young Indian consumer lens.Design/methodology/approachThe study uses an interpretive research position, employing qualitative techniques in the form of in-depth interviews. In total, 62 respondents were interviewed, and later the transcribed interviews were analyzed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…Other than that, there is also a strong correlation between acceptance and purchase intention (r = 0.611, p < 0.05). Sharma, Pradhan and Srivastava (2021) discovered that online acceptance and praise from others have grown to be important predictors of purchasing luxury products, therefore lends credence to the results of H1. Therefore, H2 is accepted.…”
Section: Correlationsmentioning
confidence: 55%
See 1 more Smart Citation
“…Other than that, there is also a strong correlation between acceptance and purchase intention (r = 0.611, p < 0.05). Sharma, Pradhan and Srivastava (2021) discovered that online acceptance and praise from others have grown to be important predictors of purchasing luxury products, therefore lends credence to the results of H1. Therefore, H2 is accepted.…”
Section: Correlationsmentioning
confidence: 55%
“…The findings of Nia and Zaichkowsky (2000) showed that the ownership of real luxury brands will make them feel admired, recognized, and accepted. Recent study by Sharma, Pradhan and Srivastava (2021) suggested that online acceptance and praise from others have also become significant predictors of Ming L.M. Int.…”
Section: Acceptancementioning
confidence: 99%
“…India is at a nascent stage in experimenting with luxury. Enhancing social identity is as important for consumers as expressing personal meanings (Sharma et al , 2021). Considering this contextual backdrop, many respondents emphasized the need for social acceptability.…”
Section: Resultsmentioning
confidence: 99%
“…First, two of the UK's largest online gun retailers' websites were reviewed to identify the most common manufacturers. Table 1 provides the list of manufacturers that were chosen, along with other pertinent company information, and following the approach of other research that explores 'luxury goods' (Sharma, Pradhan and Srivastava, 2021;Jain, 2020) was purposively sampled in order to reflect the global distribution of gun manufacture. It was not possible to review every manufacturer due to an absence of digital adverts (notably Russian manufacturers) or a lack of shotguns of comparable types (some manufacturers produce predominantly pump-action guns).…”
Section: Methodsmentioning
confidence: 99%